Project Management of the Future - Exploit the Potential of Megatrends and Digitalization - Agnes Wittrich (ZBW - Leibniz Information Centre for Economics, 2022)
The paper is a call for project performers of the future to train their sensitivity for the emerging of megatrends, to recognize their potential and to use the opportunities they offer for the further development of project management. This theoretical study applies as method the systematic literature review to show how megatrends and digital transformation impact the discipline and how their potential can be utilized for its progress. Project management cannot withdraw from influence of the megatrends. The degree of their impact on the project management processes may differ, but they constitute the framework which supports the formation of reliable predictions regarding the direction in which this discipline is moving.
Conference: PEMF Conference 2022, Poprad Economic and Management Forum, Poprad, Slovak Republik, 10th-11th November 2022
Keywords: M140; M160; 330; digitalization; megatrends; future; project management